Phytomass production from Silybum marianum for bioenergy - Sulas L.; Ventura A.; Murgia L. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Silybum marianum Gaertner is a herbaceous thorny member of the Compositae family, common in the native flora of the Mediterranean basin. Silybum marianum seeds contain a complex substance called silymarin, well appreciated for treating human liver diseases and animal wellbeing. Because of its extremely aggressive vegetative growth, causing stress on adjacent plants, it is known as a dangerous weed in cropping areas. On the other hand, the rusticity and the high growth rates of S. marianum make it interesting for bioenergy purposes in rainfed Mediterranean environments. A research work was started in Sardinia in order to evaluate the performance of this species in terms of biomass production under low input conditions. Data on undisturbed dry matter accumulation, yield, and phytomass partitioning into its components (leaves, stems and heads) were collected. The heating value and the energy balance of the crop were also assessed. The first year results are reported in this paper.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)